2004
DOI: 10.1093/jac/dkh441
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of Dhvar-5 and gentamicin in an MRSA osteomyelitis prevention model

Abstract: We conclude that both the gentamicin beads and the Dhvar-5 beads were only partially effective at preventing MRSA infection in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…It is frequently stated that one of the substantial disadvantages in the use of PMMA as an antibiotic delivery system for local treatment is the lowlevel subinhibitory release after the burst release has subsided, thereby also inducing and selecting antibiotic resistance of bacteria. 11,[13][14][15][16][17] The in vitro study performed by Bertazzoni et al [25][26][27] on different PMMA devices impregnated with the same association of antibiotics showed that (1) the release kinetics of the combination was initially high followed by sustained constant release of both antibiotics, (2) the release profile of gentamicin and vancomycin was superimposable, and (3) gentamicin release was enhanced by the presence of vancomycin. The concentrations of antibiotics eluted at different times showed effective antibacteric activity exceeding the MIC with different periods of activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is frequently stated that one of the substantial disadvantages in the use of PMMA as an antibiotic delivery system for local treatment is the lowlevel subinhibitory release after the burst release has subsided, thereby also inducing and selecting antibiotic resistance of bacteria. 11,[13][14][15][16][17] The in vitro study performed by Bertazzoni et al [25][26][27] on different PMMA devices impregnated with the same association of antibiotics showed that (1) the release kinetics of the combination was initially high followed by sustained constant release of both antibiotics, (2) the release profile of gentamicin and vancomycin was superimposable, and (3) gentamicin release was enhanced by the presence of vancomycin. The concentrations of antibiotics eluted at different times showed effective antibacteric activity exceeding the MIC with different periods of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the local application of antibiotics has clearly been demonstrated to provide higher local antibiotic concentrations than those achieved with intravenous administration and to eradicate or suppress the infection process, thus also avoiding systemic exposition to high plasma antibiotic levels that often result in various toxic side effects. [11][12][13][14][15][16] Polymethylmethacrylate (PMMA) has been the most widely studied material as a carrier for numerous antibiotics, including gentamicin, tobramycin, and vancomycin, 13,16,17 or recently the antimicrobial peptide Dhvar-5. 14 Other local drug delivery systems have been studied, such as collagen 17 and chitosan 18 impregnated with gentamicin, polymers (poly lactic-glycolic acid, poly DL lactic acid, and polycaprolactone) impregnated with tobramycin, vancomycin, or ciprofloxacin, 11,[19][20][21] ceramics (hydroxyapatite, carbonated apatite, calcium sulphate) impregnated with gentamicin, tobramycin, vancomycin, moxifloxacin, and antimicrobial peptides (human lactoferrin 1-11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The broad spectrum of Dhvar5, together with its safe cytotoxic profile, prompted its application on osteomyelitis prevention models. However, although the peptide revealed in vivo activity, it did not achieve the same treatment levels than gentamicin [12]. This situation may be associated with the pharmacokinetics challenges posed by AMP, as these are prone to undergo proteolytic degradation, self-aggregation and aggregation with plasma proteins.…”
Section: Introductionmentioning
confidence: 92%